To expand the expression \((3x - 1)(x^2 + 9x + 4)\) and write it in standard form, we'll distribute each term in the first expression to each term in the second expression.
Step 1: Distribute \(3x\) to each term in \((x^2 + 9x + 4)\)
- \(3x \cdot x^2 = 3x^3\)
- \(3x \cdot 9x = 27x^2\)
- \(3x \cdot 4 = 12x\)
This gives us: \[ 3x^3 + 27x^2 + 12x \]
Step 2: Distribute \(-1\) to each term in \((x^2 + 9x + 4)\)
- \(-1 \cdot x^2 = -x^2\)
- \(-1 \cdot 9x = -9x\)
- \(-1 \cdot 4 = -4\)
This gives us: \[ -x^2 - 9x - 4 \]
Step 3: Combine the results
Now we can combine all the terms: \[ 3x^3 + 27x^2 + 12x - x^2 - 9x - 4 \]
Step 4: Combine like terms
-
Combine \(27x^2\) and \(-x^2\): \[ 27x^2 - x^2 = 26x^2 \]
-
Combine \(12x\) and \(-9x\): \[ 12x - 9x = 3x \]
-
The constant term is -4.
Putting it all together, we get: \[ 3x^3 + 26x^2 + 3x - 4 \]
Final Answer
The expanded polynomial in standard form is: \[ 3x^3 + 26x^2 + 3x - 4 \]